DESIGN OF DIGITAL MAP BASED ON HAND GESTURE AS A PRESERVATION OF WEST JAVA HISTORY SITES FOR ELEMENTARY SCHOOL - Padmasari, Ayung Candra; Wahyuningsih, Yona; Rostika, Deti (Universitas Negeri Malang, 2019)
Social science study of historical content at present does not seem to be directly proportional to the development of the industrial revolution 4.0. it is because of rote learning styles, text-based, teacher-centered teaching methods without technologicalaided modifications. With these problems, it is necessary to have design innovations and media for learning models, one of them is to design a hand gesture-based map equipped with a leap motion controller. This study aims to design a digital hand gesture-based map design as the preservation of West Java historical sites for elementary school children. The method used in the study is Design and Development (D&D). The results of this study are the design of an interactive map as a teaching media innovation and the configuration response of the tool with the results of 13 ms / FPS 33 ms / 60 FPS tap gesture responses.